Use of test of science related attitudes (TOSRA) in Korea - Fraser, Barry; Lee, Seon (2015)
Although the Test of Science Related Attitudes (TOSRA) was developed quite some time ago, today, it continues to be frequently used by researchers and teachers around the world, in either its original form or in modified forms (Fraser, 1981). This chapter is devoted to describing the background to TOSRA, reviewing its validity and usefulness in past research internationally, and illustrating its use in one specific study. In the study reported here, the TOSRA was modified, translated into the Korean language, crossvalidated and used in a study with two aims. First we investigated differences between the attitudes of students in three different streams (humanities, science-orientated and science-independent). Second, we explored associations between students’ attitudes and the constructivist orientation of their classroom learning environments (using the Constructivist Learning Environment Survey, CLES).